(untitled) (Research, Society and Development, 2022)
Violence is a serious public health problem due to the increase in morbidity and mortality rates related to this issue. As the school is an important space for the development and deepening of knowledge and changes; it is a propitious and suitable place for the implementation of educational actions in different areas. For young people, misinformation is something significant, considering the lack of specific knowledge about a particular issue, and the lack of ability to deal with difficulties that may arise in relation to a particular problem in their daily lives. Aiming to know the knowledge among young adolescents about violence against women, this study firstly carried out a socioeconomic survey and the second step was to analyze the level of knowledge about violence against women among young adolescents between 15 and 19 years old (UN). This survey was conducted through a virtual questionnaire, because the research was conducted during the pandemic period of COVID-19, which consists of closed questions where the student will have the option to agree, disagree or indicate not knowing about the questioned information. It was observed that although the participants already had contact with the theme, they showed that the knowledge acquired was not fully effective. It is hoped that this study will contribute to the reduction of the rates of violence against women, emphasizing the fundamental roles of nurses in the orientation, prevention, promotion and recovery of health, especially nurses with a forensic specialty who are more qualified to deal with the expressed theme.